Evidence of Unprecedented High Electronic Conductivity in Mammalian Pigment Based Eumelanin Thin Films After Thermal Annealing in Vacuum - Migliaccio, Ludovico; Manini, Paola; Altamura, Davide; Giannini, Cinzia; Tassini, Paolo; Maglione, Maria Grazia; Minarini, Carla; Pezzella, Alessandro (Frontiers in Chemistry, 2019)
Melanin denotes a variety of mammalian pigments, including the dark electrically conductive eumelanin and the reddish, sulphur-containing, pheomelanin. Organic (bio)electronics is showing increasing interests in eumelanin exploitation, e.g. for bio-interfaces, but the low conductivity of the material is limiting the development of eumelanin-based devices. Here, for the first time, we report an abrupt increase of the eumelanin electrical conductivity, revealing the highest value presented to date of 318 S/cm. This result, obtained via simple thermal annealing in vacuum of the material, designed on the base of the knowledge of the eumelanin chemical properties, also discloses the actual electronic nature of this material’s conduction.